2D Interpretation Of Controlled Source Audio Magnetotelluric (CSAMT) Data Integrated With Borehole Data In Kamojang Geothermal Field West Java, Indonesia. (January 2019) - Susilawati,; Mustopa, Enjang Jaenal
Abstract: CSAMT is the one of electromagnetic method which uses unnatural source grounded dipole with the range of frequency between 0.1Hz-10 kHz. In order to qualify the response measured is plan wave, then the corrected source effect. The objective of this study was to obtain that have been corrected for source to have the same characteristic as MT data. CSAMT data that has been corrected, subsequently inverted to get the exact model and validated to well log data in the form of temperature data. After interpretation found that the some of the line measurement at geothermal field Kamojang has two layers. There are seven line, line-1 until line-7, line-2 until line-7 have the characteristic of geothermal, the first layer has a resistivity of 3-15 Ω.m and the average of thickness of 400-1500 meters. The second layer has a resistivity value of 20-300 Ω.m that is more resistive than the first layer, except for line 1, there is no low resistivity in the first layer. The first layer is a layer of clay, identified with resistivity values ranging from 2, 5 - 15 Ω.m with 900-1400m thickness with temperature data on KMJ-12 range 180-200°C, and the next layer is more resistive layer than the second layer is 18 Ω.m -100 Ω.m with temperature data at KMJ-53 at a depth of 710 meters is 240°C.